IMPLEMENTASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM MENUNJANG PERWUJUDAN AKUNTABILITAS DAN TRANSPARANSI LAPORAN KEUANGAN DESA WRINGINREJO KECAMATAN GAMBIRAN KABUPATEN BANYUWANGI - Ningrum, Arni Tia; Handayani, Yuniorita Indah; Ningsih, Wiwik Fitria (RISTANSI: Riset Akuntansi, 2025)
This study aims to examine the implementation and impact of the Village Financial System (Siskeudes) in supporting transparency and accountability in the financial reporting of Wringinrejo Village, Gambiran Subdistrict, Banyuwangi Regency. A qualitative approach was used, relying on primary and secondary data collected through observation, interviews, and documentation. Informants in this research included the Village Head, Village Secretary, and the Heads of Finance, Planning, and Administration. A purposive sampling technique was employed to select informants. The findings indicate that the implementation of Siskeudes has been effective, fostering coordination among village officials in managing finances transparently and accountably. Although there were minor challenges, such as limited understanding of the application, these were manageable by the village administration. Overall, the use of Siskeudes has had a positive impact by making financial management and reporting more practical, secure, and efficient.